Carvone Attenuates Irinotecan-Induced Intestinal Mucositis and Diarrhea in Mice - Abbas, Ban Walid; H. Kathem, Sarmed (Iraqi Journal of Pharmaceutical Sciences, 2021)
Intestinal mucositis is referring to inflammatory or ulcerative lesions of the oral or gastrointestinal tract; one of the main reasons is treatment with cancer chemotherapy. The prodrug Irinotecan is converted by carboxylesterase to the active metabolite SN-38, conjugated by UGT enzyme to SN-38G and then deconjugated by ?-glucoronidase produced by intestinal bacterial flora to produce SN-38. Irinotecan induces intestinal mucositis and diarrhea due to increased concentration of its active metabolite (SN-38).To evaluate the protective effect of carvone, I.P injection of (75mg/kg/day) of irinotecan for 4 days to induce intestinal mucositis, carvone administered to mice orally for 6 days starting from day 1. Results showed that carvone (50mg/Kg and 100mg/Kg) significantly and by dose-dependent manner attenuated body weight loss (-9.39±1.56 vs. -23.21±1.65 %), diarrhea scores (0.50±0.244 vs. 2.67±0.211) and serum TNF-? level (1361.44±55.075 vs. 3402.12±321.56 ng/ml) compared to experimental model group. In conclusion, carvone exerted a dose dependent anti-inflammatory and protective effect by attenuation irinotecan-induced intestinal mucositis.